Advances in industrial and labor relations - Gollan, Paul; Lewin, David 1943- (Emerald, 2015)
Advances in industrial and labor relations is a refereed research volume published annually or biannually. Although the series is designed to focus on industrial relations issues,volumes also focus on diverse disciplines, such as economics, law, history, organizational behavior, psychology, and sociology.